Rancang Bangun Sistem Detectoring dan Monitoring Push-Up Berbasis IOT - Muhammad Adam Akbar; Lilik Anifah; Nur Kholis; Nurhayati Nurhayati (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Push Up is a physical activity carried out by individuals that aims to strengthen the muscles of the body, namely the muscles of the arms, shoulders and chest. Designing an IOT-based detection and monitoring system with the aim of making it easier for tool users to know the number of repetitions and the number of calories used automatically. Detectoring with the help of four proximity sensors to detect motion when doing push-ups and monitoring using an android application made specifically for the device. The component used is NodeMCU ESP8266 as a microcontroller. The parameters displayed in the application include a column of push-up repetitions, a column for the number of calories used, and a graph of increasing push-up repetitions. The tool testing method was carried out 15 times for data collection with 20 push-up repetitions for each data collection. The results of the test, obtained an error percentage of 1.33%. So that this tool can help users to monitor the repetitions that have been done and find out the amount of calories used.